Pelatihan Tajahizul Mayit Sebagai Wujud Pengimplementasian Ilmu Agama pada NNB Simarloting - Mhd Sholihin Martua Lubis; Marni Marni; Nur Annisa; Nur Fadilah; Nur Hidayah; Robiyatul Adawiyah; Sulaiman Sulaiman; Sholatiah Lubis; Siti Banun (Jurnal Kabar Masyarakat, 2024)
In this community service activity, researchers provide assistance on important issues related to human relationships with other humans, namely the issue of tajhizul deceased (care of corpses). Islam pays very serious attention to this issue, so this is one of the obligations that must be fulfilled by humanity, especially Muslims. This service work aims to 1). Providing to equip Naposo Nauli Bulung in Sampuran Simarloting Village with tajhizul mayit skills, 2). train Naposo Nauli Bulung so they can implement and develop religious knowledge. Meanwhile, the benefits that will result from this training are 1). Improving the skills of the Naposo Nauli Bulung in handling corpses properly and correctly in accordance with the teachings of Islamic law, so that if one day they are needed they are ready to use them. 2). Increase in skilled personnel in handling corpses. 3). Increased skills of the Modins in handling corpses. Naposo Nauli Bulung has been able to implement and practice methods of handling corpses properly and correctly in accordance with the provisions of Islamic law. The research method in this activity is the Participatory Action Research (PAR) method. Apart from the PAR method, we also conducted observations and interviews. From the assistance in the implementation of tajhizul corpse training which was carried out in Sampuran Simarloting village with the training target, Nauli Bulung naposos have been able to practice how to handle corpses properly and correctly in accordance with the provisions of Islamic law.